Delayed Vestibular Schwannoma Regrowth Following Shrinkage After Stereotactic Radiosurgery: Implication for Life-Long Surveillance. Issue 2 (February 2017) - Stapleton, Emma; Crowther, John A.; Locke, Richard; Kontorinis, Georgios
Abstract : Objective: To enhance understanding of the behavior of vestibular schwannomas (VS) after stereotactic radiosurgery (SRS), including the potential for late tumor regrowth, and the need for lifelong radiological and clinical surveillance. Patients: From a total of 540 patients with VS and out of 95 patients receiving SRS for their growing VS, the cases of two women patients aged 58 and 59 years with medium sized, growing VS are presented. Intervention: Both patients were treated with SRS. Following treatment, both patients had close clinical follow-up and serial magnetic resonance imaging (MRI). Main Outcome Measures: Post-SRS clinical assessment and serial MRI to determine VS size and respond to treatment. Results: Close clinical follow-up after SRS identified no change in symptoms in one patient; the other developed ipsilateral facial nerve twitching without weakness. Serial MRI identified that in both patients, VS that had initially decreased in size following SRS, exhibited significant late regrowth after a 3-year period, reaching the pretreatment size. Conclusions: This is the first report of late vestibular schwannoma regrowth following a period of significant shrinkage after SRS. Potential reason may be the presence of living cells within the tumor; the possibility of malignant transformation should also be taken into account. Following SRS, patients with VS warrant lifelong radiological and clinical surveillance, even following good response, as there seems to be a small chance of initial regression followed by further growth. Microsurgery for tumor removal and histological diagnosis is indicated in such cases.